Strategic information system agility : from theory to practices - Sahid, Abdelkebir; Maleh, Yassine; Belaissaoui, Mustapha (Emerald Publishing Limited, 2020)
Ensuring an efficient and agile information system in organizations is a real challenge. Only an agile IT strategy can underpin this. Strategic Information System Agility offers methodological and practical support to achieve effective IT agility in complex and dynamic environments.